2013
DOI: 10.1186/1472-6750-13-110
|View full text |Cite
|
Sign up to set email alerts
|

Construction of fast xylose-fermenting yeast based on industrial ethanol-producing diploid Saccharomyces cerevisiaeby rational design and adaptive evolution

Abstract: BackgroundIt remains a challenge for recombinant S. cerevisiae to convert xylose in lignocellulosic biomass hydrolysates to ethanol. Although industrial diploid strains are more robust compared to laboratory haploid strains, however, industrial diploid S. cerevisiae strains have been less pursued in previous studies. This work aims to construct fast xylose-fermenting yeast using an industrial ethanol-producing diploid S. cerevisiae strain as a host.ResultsFast xylose-fermenting yeast was constructed by genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 33 publications
3
60
0
1
Order By: Relevance
“…Furthermore, adaptation strategy also stabilizes heterologous gene expression in mutant strains (Diao et al, 2013;Lee et al, 2014). In the similar way, ethanol yield has also been augmented about twofold in recombinant S. cerevisiae after adaptation in bagasse hydrolyzate containing inhibitors including furaldehydes, phenolic compounds, and aliphatic acids (Martin et al, 2007).…”
Section: −1mentioning
confidence: 67%
“…Furthermore, adaptation strategy also stabilizes heterologous gene expression in mutant strains (Diao et al, 2013;Lee et al, 2014). In the similar way, ethanol yield has also been augmented about twofold in recombinant S. cerevisiae after adaptation in bagasse hydrolyzate containing inhibitors including furaldehydes, phenolic compounds, and aliphatic acids (Martin et al, 2007).…”
Section: −1mentioning
confidence: 67%
“…Numerous follow-up studies identified extra genetic perturbations that enhanced xylose fermentation by engineered S. cerevisiae (Diao et al, 2013;Hahn-Hagerdal et al, 2007;Hasunuma et al, 2014;Kim et al, 2013b;Kim et al, 2013c;Kuyper et al, 2005a;Lee et al, 2014b;Matsushika et al, 2009;Ni et al, 2007). The step most speculated to be limiting for efficient xylose metabolism was the PPP, where xylulose-5-phosphate is metabolized into intermediates of glycolysis, fructose-6-phosphate and glyceraldehyde-3-phosphate (Diao et al, 2013;Kim et al, 2013b;Matsushika et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…The imbalance in redox metabolism caused by the different coenzyme preferences between XR and XDH result in the accumulation of the byproduct xylitol and a lower ethanol yield; cofactor engineering resulted in limited improvement (Hou et al 2009a; Zha et al 2012; Zhang et al 2010). For the XI pathway, since xylose is directly isomerized to xylulose with no coenzyme participation, incorporating this pathway is a direct and effective strategy for initiating xylose metabolism in S. cerevisiae (Demeke et al 2013; Diao et al 2013; Zhou et al 2012). Highly efficient XI activity is a prerequisite for rapid and efficient xylose fermentation in S. cerevisiae (Brat et al 2009; Kuyper et al 2003; Madhavan et al 2009; Walfridsson et al 1996; Zhou et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Normally, xylose is absorbed non-specifically and insufficiently by hexose transporters and is competitively inhibited by glucose in S. cerevisiae (Subtil and Boles 2012). Therefore, to address this problem, both wild-type and mutated endogenous and heterologous transporters were screened (Diao et al 2013; Farwick et al 2014; Moon et al 2013; Nijland et al 2014; Runquist et al 2009; Shin et al 2015; Wang et al 2015, 2016). Moreover, with higher efficiency and/or specificity for xylose, a transporter lacking glucose inhibition may relieve the glucose repression effect in a xylose absorption node, thereby increasing xylose metabolism.…”
Section: Introductionmentioning
confidence: 99%